Chasing the mafia : 'ndrangheta, memories and journeys - Sergi, Anna (Bristol University Press, 2022)
The ‘ndrangheta--the Calabrian region of Italy's mafia--is one of wealthiest and most powerful criminal organizations today. It is considered Italy's most powerful mafia; it's not only the main object of concern for anti-mafia units in Italy, but also for joint investigative teams in Europe and beyond. Combining autobiography, travel ethnography, memoir, academic rigour and investigative journalism, this book provides a global outlook on the ‘ndrangheta, taking the reader to small villages and locations in Italy and abroad to Australia, Canada, United States and Argentina--Publisher description.